Quantitative Determination of Naltrexone Hydrochloride in a Nasal Spray by High-performance Liquid Chromatography - Yu. M. Domnina; V. V. Suslov; S. A. Kedik; E. V. Vorfolomeeva; A. V. Meleshko (Разработка и регистрация лекарственных средств)
Introduction. Naltrexone, an antagonist of µ-opioid receptors, is promising for the treatment of various autoimmune and oncological diseases when used in doses of 1.5–5 mg/day. To date, there are no medications that provide such dosages of naltrexone.Aim. Development and validation of a method for the quantitative determination of naltrexone hydrochloride in a nasal spray by high performance liquid chromatography (HPLC).Materials and methods. As an object of research, a naltrexone hydrochloride nasal spray was used. The quantitative determination of naltrexone in the test sample was developed using a Dionex UltiMate 3000 high-performance liquid chromatograph (Thermo Scientific, USA) equipped with a diode-matrix detector.Results and discussion. The possibility of using isocratic and gradient chromatographic modes for the quantitative determination of naltrexone hydrochloride in the nasal spray was studied. Based on these results, a new method of determination using the gradient mode is proposed, which allows minimizing the influence of the polymer component in the test sample on the analysis results.Conclusion. A new technique of high-performance liquid chromatography (HPLC) is proposed that allows identification and quantification of naltrexone hydrochloride in a nasal spray containing a high concentration of water-soluble heat-sensitive poloxamer as a thickener. The developed method was validated according to the parameters: correctness, precision, specificity, linearity.